2018
DOI: 10.3390/su10061692
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Government Subsidies on Manufacturing Innovation: Evidence from the New Energy Vehicle Industry in China

Abstract: Manufacturing innovation is of strategic importance to China in its effort to reshape future technology. This study explores the impact of government subsidies on the research and development (R&D) intensity of China's new energy vehicle (NEV) enterprises. The dynamic relationship between government subsidies and R&D intensity is tested with a panel regression model and a threshold regression model. We find that government subsidies have a significantly positive impact on R&D intensity when considering the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 37 publications
5
54
0
Order By: Relevance
“…Similarly, Lee and Cin [14] pointed out that government subsidies were beneficial to the R&D investment of Korean small and medium-sized enterprises. Jiang et al [15] found that government subsidies had a significantly positive impact on R&D intensity of China's new energy vehicle enterprises. Other scholars [9,[16][17][18][19][20] also found that direct government funding stimulated private R&D investments.…”
Section: Relationship Between Government Subsidies and Randd Investmentmentioning
confidence: 99%
“…Similarly, Lee and Cin [14] pointed out that government subsidies were beneficial to the R&D investment of Korean small and medium-sized enterprises. Jiang et al [15] found that government subsidies had a significantly positive impact on R&D intensity of China's new energy vehicle enterprises. Other scholars [9,[16][17][18][19][20] also found that direct government funding stimulated private R&D investments.…”
Section: Relationship Between Government Subsidies and Randd Investmentmentioning
confidence: 99%
“…(1) Governments have two strategies: they either choose the price subsidy policy or choose the R&D subsidy policy. Government subsidies can be divided into industrial subsidies and consumption subsidies in China [7]. To support the healthy development of the NEV market and reduce pollution from vehicle exhaust, the government subsidises enterprises and consumers who purchase NEVs through R&D subsidies for enterprises and price subsidies for consumers.…”
Section: Model Assumptions and Formulationmentioning
confidence: 99%
“…The evolution process of the three parties is shown in Figure 2. For governments, the price subsidy policy is still the best subsidy policy in the NEV market [7]. Over time, the number of governments choosing price subsidies in the market steadily increases.…”
Section: Effect Of the Initial Market Proportions Of The Three Partiementioning
confidence: 99%
See 1 more Smart Citation
“…The literature on the effect of subsidies on innovative firms began in the 2000s, seeking to determine if there was a crowding-out effect on the companies internal R&D expenditure. In general, these studies found this effect is positive, and firms receiving subsidies end up spending a higher amounts of R&D than they would have spent without the subsidy, that is, the so-called input additionality effect (Aerts & Czarnitzki, 2004;Aerts & Schmidt, 2008;Almus & Czarnitzki, 2003;Busom, 2000;Cerulli & Potì, 2008Choi & Lee, 2017;Chudnovsky, Lopez, Rossi, & Ubfal, 2006;Cin, Kim, & Vonortas, 2017;Czarnitzki & Delanote, 2015;Czarnitzki, Ebersberger, & Fier, 2007;Czarnitzki & Hussinger, 2018;Czarnitzki & Lopes-Bento, 2012Engel, Rothgang, & Eckl, 2016;González & Pazó, 2008;Görg & Strobl, 2007;Heshmati & Lööf, 2005;Jiang et al, 2018;Lach, 2002;Sanguinetti, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%